Gastroenteritis. Issue 11 (November 2022) - Dawson, Tom; Ratcliffe, Anna; Onyon, Clare
Abstract: Gastroenteritis is a major cause of mortality worldwide and a common reason for hospitalization in children, with young children, under 5 years of age, being disproportionally affected. This article reviews the burden of acute gastroenteritis, some prevention strategies including rotavirus vaccination, as well as an approach to history, examination and treatment. The text also considers common differential diagnoses for this condition and the use of telephone triage, history and examination to assess the degree of dehydration. Investigations are not usually required but may guide treatment in some circumstances. Oral Rehydration Therapy (ORT) can be used in the majority of cases and approaches to rehydration are detailed. Treatment options including the use of antiemetic treatment and probiotics are outlined. Children with severe dehydration often require IV therapy. The importance of careful sodium monitoring and the risks associated with IV rehydration are also addressed.